Evaluation of Isooxazoline derivatives in the Treatment of Canine Demodicosis - Pardeep Sharma; Abhishek Bansal (The Indian Veterinary Journal, 2023)
Canine demodicosis is a common dermatological condition observed indogs. The aim of this study was to evaluate the effectiveness of isooxazoline derivatives for the treatment of demodicosis compared to ivermectin.Forty-one dogs with demodicosis were treated with ivermectin (n=13), fluralaner(n=5), sarolaner(n=11) and afoxolaner (n=12),respectively. The mite count was evaluated on day 0, 28, 56 and 84 of treatment period. A single oral dose of isooxazoline derivatives reduced Demodex mite counts in skin scrapings by an average of 98.6% in all dogs by 28th day and 100% by 84th day. Single administration of ivermectin resulted to be only 76.8% effective. No adverse effects of drugs were observed in any of the dogs.